Jumping to conclusions in autism: integration of contextual information and confidence in decision-making processes. - Sahuquillo-Leal, Rosa; Ghosn, Farah; Moreno-Giménez, Alba; Almansa, Belén; Serrano-Lozano, Elena; Ferrín, Maite; Cañada-Martínez, Antonio; Vento, Máximo; García-Blanco, Ana (European Child & Adolescent Psychiatry, 2020)
Individuals with Autism spectrum condition (ASC) present cognitive biases and a difficulty to integrate emotional responses in decision-making, which is necessary for adequate social functioning. Thus, understanding the underlying mechanisms of the altered decision-making in individuals with ASC may eventually have a positive impact on their social functioning. The Picture decision task was employed to observe the effect of new information (fragments of an incomplete picture), interpretative context (verbal cues), and the level of confidence on decision-making processes. Our study administered the task to 49 children with ASC and 37 children with Typical Development (TD). Children with TD showed a higher probability of success when an interpretative context was given. Conversely, children with ASC had an equal probability of success regardless of whether an interpretative context was provided or not. In addition, unlike children with TD, the level of confidence did not allow predicting the probability of successful decisions in children with ASC. Finally, children with ASC had more probability of jumping to conclusions, a decision made quickly with only one fragment of the picture while being completely sure of it. These results are discussed in light of current cognitive and emotional theories on ASC.